PP.17.26: ASSESSMENT OF 24-HOUR BLOOD PRESSURE VARIABILITY AND ITS RELATIONSHIP WITH BLOOD PRESSURE VALUES IN TREATED HYPERTENSIVE PATIENTS. (June 2015) - Magdás, A.; Belényi, B.; Varga, A.; Gliga, M.L.; Podoleanu, C.; Incze, A.
Abstract : Objective: Average real variability (ARV), as a reliable index has been proposed to define blood pressure oscillations occurring trough 24-hour, but a normal range or cut off point has not been established. Therefore, the aim of the present study is to define low, medium and high variability range and to assess the relationship between these groups of variability and blood pressure values. Design and method: This observational study was conducted between 2012–2014 in County Clinical Hospital- Department for Internal Medicine IV, Targu-Mures, Romania and included 102 patients with treated hypertension. Circadian blood pressure was recorded with a validated 24-hour ambulatory monitoring device (Meditech 05 ABPM). Blood pressure variability was calculated according to the formula of average real variability, using a computerized soft. Based on variability, patients were divided in to low, medium or high variability group. Blood samples were collected regarding cardiovascular risk factors (total cholesterol, triglycerides, blood glucose, creatinine). Characteristics of the groups were compared by one way-ANOVA test, correlations were analysed with Pearson's test, categorical variables were compared with chi 2 test, using Graph Pad Prism 5 statistical program. Results: Low variability was defined as ARV between 4.32–9.85 mmHg (34 patients), medium 9.86–12.87 mmHg (45 patients), high variability between 12.88–16.87 mmHg (23 patients). Mean age was statistically significant among the groups, 57.02 ± 13.52, versus 62.42 ± 11.01 versus 65.69 ± 13.1 years, p = 0.02. The 24-hour systolic blood pressure differed significantly between the groups, 131, 38 ± 16.31 versus 136, 13 ± 12.04 versus140.9 ± 12.21, p = 0.037. Although, glomerular filtration rate was lowest in the high variability group 71, 12 ± 28, 91 the difference was statistically not significant (p = 0.88). In the high variability group positive correlation was found between blood pressure variability and 24-hour systolic blood pressure (p = 0.02, r 2  = 0.2196, CI:0.06984 to 0.7383). Conclusions: High blood pressure variability could be defined as ARV greater than 12.88 mmHg. Elderly patients show greater blood pressure values, higher blood pressure variability and impaired kidney function. To prevent end organ damage, evaluation and reduction of blood pressure variability could be at least as important as blood pressure lowering.